PROFESSIONAL TRAINING FUTURE TEACHERS OF MUSIC ART TO VOCAL AND EDUCATIONAL ACTIVITIES: REGULARITYS, PRINCIPLES - Ovcharenko, Natalia (Continuing Professional Education: Theory and Practice, 2019)
The article substantiates the relevance of the study of patterns and principles of training of future teachers of music to vocal and educational activities. It is analyzed scientific works on philosophy, philosophy of education and the arts, education, music pedagogy and music. The author displays deterministic relationship between the philosophical, pedagogical and artistic laws and the laws and principles of future teachers of music training to vocal and educational activities. It is determined that all philosophical, pedagogical or artistic law inherent in certain laws and principles; knowledge of laws to make the process of preparation of teachers of music more productive and manageable. The author classified laws and principles of training of future teachers of music to vocal and educational activities specifically to common didactic and professional. Specific professional patterns include: interdependence of vocal psychological and physiological processes; the relationship between the value attitude to vocal teacher and educational activities and the nature of art and the aesthetic impact of vocal art and vocal pedagogy. Specific professional principles include: various types and forms of vocal and educational activities, and cultural; psycho-physiological conditioning; semiotic focus and interpretation of the text of a musical work; creative performance; consideration of teaching experience.